Perbandingan Kebijakan Hukuman Mati Di Indonesia Dan Belanda: Perspektif Pemidanaan Dan Hak Asasi Manusia - Randi Putra Ramadhan (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Capital punishment remains one of the most controversial issues in criminal law systems across nations. Indonesia, which retains the death penalty, and the Netherlands, which abolished it in 1870, represent a highly relevant comparative study, especially since Indonesian law was largely inherited from the Dutch colonial legal system. This study comparatively analyzes capital punishment policies in both countries from the perspectives of penology and human rights protection using normative legal research and a comparative law approach. The findings reveal fundamental differences in the penological philosophies of both nations: Indonesia adheres to a retributive theory that justifies capital punishment, while the Netherlands has fully transitioned to rehabilitation and resocialization theories. Regarding human rights, the Netherlands is bound by the European Convention on Human Rights (ECHR), which strictly prohibits capital punishment, whereas Indonesia upholds national legal sovereignty. The study recommends that Indonesia consider a moratorium on the death penalty as an initial step toward a more humane criminal justice reform.